Implementation Of Drinking Boiled Celery Leaf Water Therapy To Lower Blood Pressure In Hypertension Patients Through The Application Of The Florence Nightingale Theory Model In The Work Area Of The Jembatan Kecil Community Health Center In Bengkulu City In 2025 - Yuspita , Serli; Pebriani, Emi (Utami Publisher, 2026)
Indonesian Health Survey (2023) prevalence of hypertension in Indonesia based on doctor's diagnosis with estimated number of hypertension cases 638,178. men 321,060 women 317,118. based on age 25-34 years is the highest hypertension sufferer of 133,887. The purpose of this study is that researchers are able to reduce blood pressure in hypertensive patients through the application of the Florence Nightingale theory model in the Work Area of ​​the Jembatan Kecil Health Center, Bengkulu City in 2025. Nursing care used uses case study research by applying celery boiled water therapy in reducing blood pressure in patients with hypertension through the application of Florence Nightingale theory with the number of participants in this study 2 people with the same case, namely with hypertension nursing problems. The results of the application of celery boiled water therapy are very effective in reducing blood pressure through the application of Florence Nightingale theory. Florence Nightingale's theory can be applied and applied well in treatment focused on cases of hypertension patients. Researchers advise patients and their families to maintain their health, both physical, psychological and environmental, and to continue to follow the recommendations that have been given and to implement and apply everything that has been taught to help patients and their families achieve optimal health.